Analysis of Factors Affecting the Adoption and Use of Environmental Management Accounting to Provide a Conceptual Model - Karimi, Zohre; Dastgir, Mohsen; Saleh, Mehdi Arab (International Journal of Economics and Financial Issues, 2017)
The present study examines and modeling the factors influencing the use of environmental management accounting tools from the financial managers and assistants point of view, who are in the oil refining and petrochemical companies. For this purpose, five main hypotheses have been developed and tested by using questionnaire. The result of this test by using, confirmatory factor analysis and structural equation test showed that from financial managers and assistants’ point of view, resistance to change, lack of standards and methods for gathering and allocation of environmental costs and lack of standards, competitive environment and society culture in dealing with environmental issues are the factors that influence the use of environmental management accounting tools. The result of the fifth hypothesis test showed that except sex, all of the personal characteristic of managers and assistants like professional work experience, field of study, academic paper and age have meaningful influence on the financial managers and assistants’ point of view in the ratio of some effective factors in using the environmental management accounting tools. Keywords: environmental management accounting, oil refining company, path analysis. JEL Classifications: C32; O13; O47